“STRATEGI PENGEMBANGAN UMKM MELALUI DIGITAL MARKETING DI DESA LEWOMADA” - Nunsio Handrian Meylano; Dimas Realino; Viktor Eko Transilvanus (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a highly strategic role in economic development in Indonesia. According to data from the Ministry of Cooperatives and SMEs, MSMEs contribute more than 60% to Indonesia's Gross Domestic Product (GDP) and employ nearly 97% of the total workforce. MSMEs also serve as the backbone of the national economy, particularly in creating new jobs and driving the economy in rural areas. Amidst the challenges of globalization and technological development, MSMEs are required to continuously adapt to compete in both domestic and international markets. With this program, it is hoped that MSMEs in Lewomada Village will not only be able to survive the competition but also thrive and become a driving force for the village economy. Furthermore, this program is also expected to encourage Lewomada Village to become a successful example of digital-based MSME development in rural areas. The goal of this activity is to equip participants from each MSME group with knowledge and expertise in marketing management and to provide them with the skills and knowledge to carry out their role as business actors professionally through digital marketing development strategies. MSMEs in Lewomada Village have significant potential for growth through digital marketing. Increased knowledge of social media, marketplaces, and digital marketing strategies provides new opportunities to reach a wider market and increase revenue. However, successful digital marketing implementation still faces challenges such as limited internet infrastructure, technical capabilities, and consistency in implementing digital marketing strategies. With proper management and ongoing support, MSMEs in Lewomada Village can develop and become more competitive in the digital era